2016
DOI: 10.1016/j.jchf.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Corin as a Predictor of Cardiovascular Events in Patients With Chronic Heart Failure

Abstract: Our study demonstrates that plasma corin is a valuable prognostic marker of MACE in patients with CHF, independent of established conventional risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 20 publications
(6 reference statements)
1
30
0
1
Order By: Relevance
“…Spatially, corin was reduced in the infarct area and the ischemic border zone, when compared to areas remote from the ischemic zone, as demonstrated by specific immunostaining. Prior studies showed both plasma and cardiac corin levels were lower in chronic heart failure patients and experimental heart failure models [ 4 , 7 10 , 15 , 27 ] and the trend of changes in plasma and cardiac corin levels was consistent. Given the marked decline in cardiac corin expression, the possible reason for increases in plasma corin levels appear to be enhanced release of corin from ischemic or infarcted myocytes.…”
Section: Discussionsupporting
confidence: 53%
“…Spatially, corin was reduced in the infarct area and the ischemic border zone, when compared to areas remote from the ischemic zone, as demonstrated by specific immunostaining. Prior studies showed both plasma and cardiac corin levels were lower in chronic heart failure patients and experimental heart failure models [ 4 , 7 10 , 15 , 27 ] and the trend of changes in plasma and cardiac corin levels was consistent. Given the marked decline in cardiac corin expression, the possible reason for increases in plasma corin levels appear to be enhanced release of corin from ischemic or infarcted myocytes.…”
Section: Discussionsupporting
confidence: 53%
“…Converging lines of evidence from clinical and translational studies have shown that genetic abnormalities and reduction in corin cardiac expression level negatively affect DCM and HFrEF outcomes. Cardiac transcripts and circulating levels of corin are depressed in patients and translational animal models with DCM and HFrEF [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]35,36,51], and are pathologically modulated in DCM before the onset of edema and other clinical signs and symptoms of HFrEF [22,23]. In a translationally relevant mouse model of DCM-HFrEF with reduced cardiac and plasma corin levels, we reported that genetic restoration of cardiac-specific catalytically active, native corin improved systolic function, reduced myocardial fibrosis, decreased edema, and prolonged survival [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence in humans and experimental models suggests that corin, a cardiac transmembrane II serine protease, plays diagnostic, prognostic, and protective roles in DCM and HFrEF development [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Cardiac corin is co-expressed with pro-atrial natriuretic peptide (pro-ANP) and localized on the cardiomyocyte surface [25,26], where it cleaves/activates secreted pro-ANP generating biologically active ANP peptides.…”
Section: Introductionmentioning
confidence: 99%
“…In African Americans, for example, a corin variant with reduced pro‐ANP processing activity is associated with hypertension and cardiac hypertrophy (Dries et al., ; Rame et al., ). More recently, low plasma or serum corin levels have been reported in patients with heart failure (Dong et al., ; Ibebuogu, Gladysheva, Houng, & Reed, ; Zhou et al., ), coronary artery disease (Barnet et al., ; Peleg, Ghanim, Vered, & Hasin, ), myocardial infarction (Zhang et al., ; Zhou et al., ), and stroke (Hu et al., ; Peng et al., ), suggesting that corin deficiency may contribute to major cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%